Intensive glycemic control after heart transplantation is safe and effective for diabetic and non‐diabetic patients. (10th April 2013) - Garcia, Cristina; Wallia, Amisha; Gupta, Suruchi; Schmidt, Kathleen; Malekar‐Raikar, Shilpa; Johnson Oakes, Diana; Aleppo, Grazia; Grady, Kathleen; McGee, Edwin; Cotts, William; Andrei, Adin‐Cristian; Molitch, Mark E.
Abstract Some studies have shown increased mortality, infection, and rejection rates among diabetic (DM) compared to non‐diabetic (non‐DM) patients undergoing heart transplant (HT). This is a retrospective chart review of adult patients (DM, n = 26; non‐DM, n = 66) undergoing HT between June 1, 2005, and July 31, 2009. Glycemic control used intravenous (IV) and subcutaneous (SQ) insulin protocols with a glucose target of 80–110 mg/dL. There were no significant differences between DM and non‐DM patients in mean glucose levels on the IV and SQ insulin protocols. Severe hypoglycemia (glucose <40 mg/dL) did not occur on the IV protocol and was experienced by only 3 non‐DM patients on the SQ protocol. Moderate hypoglycemia (glucose >40 and <60 mg/dL) occurred in 17 (19%) patients on the IV protocol and 24 (27%) on the SQ protocol. There were no significant differences between DM and non‐DM patients within 30 d of surgery in all‐cause mortality, treated HT rejection episodes, reoperation, prolonged ventilation, 30‐d readmissions, ICU readmission, number of ICU hours, hospitalization days after HT, or infections. This study demonstrates that DM and non‐DM patients can achieve excellent glycemic control post‐HT with IV and SQ insulin protocols with similar surgical outcomes and low hypoglycemia rates.